A genomic map of climate adaptation in Mediterranean cattle breeds. Issue 5 (1st April 2019) - Flori, Laurence; Moazami‐Goudarzi, Katayoun; Alary, Véronique; Araba, Abdelillah; Boujenane, Ismaïl; Boushaba, Nadjet; Casabianca, François; Casu, Sara; Ciampolini, Roberta; Coeur D'Acier, Armelle; Coquelle, Corinne; Delgado, Juan‐Vicente; et al.
Abstract: Domestic species such as cattle ( Bos taurus taurus and B. t. indicus ) represent attractive biological models to characterize the genetic basis of short‐term evolutionary response to climate pressure induced by their post‐domestication history. Here, using newly generated dense SNP genotyping data, we assessed the structuring of genetic diversity of 21 autochtonous cattle breeds from the whole Mediterranean basin and performed genome‐wide association analyses with covariables discriminating the different Mediterranean climate subtypes. This provided insights into both the demographic and adaptive histories of Mediterranean cattle. In particular, a detailed functional annotation of genes surrounding variants associated with climate variations highlighted several biological functions involved in Mediterranean climate adaptation such as thermotolerance, UV protection, pathogen resistance or metabolism with strong candidate genes identified (e.g., NDUFB3, FBN1, METTL3, LEF1, ANTXR2 and TCF7 ). Accordingly, our results suggest that main selective pressures affecting cattle in Mediterranean area may have been related to variation in heat and UV exposure, in food resources availability and in exposure to pathogens, such as anthrax bacteria ( Bacillus anthracis ). Furthermore, the observed contribution of the three main bovine ancestries (indicine, European and African taurine) in these different populations suggested that adaptation to local climate conditions may have either relied on standing genomic variation of taurine origin, or adaptive introgression from indicine origin, depending on the local breed origins. Taken together, our results highlight the genetic uniqueness of local Mediterranean cattle breeds and strongly support conservation of these populations.